On the 100th anniversary of publishing Smuška terminologija: Design and terminographic elements - Atelšek, Simon (Slavia Centralis, 2022)
In the first part of the article we present the history, the rationale for publishing Smuška terminologija (1921) and the methodology for collecting skiing terms. In the second part, we discuss terminographic elements, and present the many elements specific for terminological dictionaries that we find in this work, although the author describes it as a collection. At the level of microstructure, we can see that the author consistently gives grammatical information for the single-word headwords that occur most frequently. Relatively consistently, he also gives definitions, which, in some cases, define the term very precisely, and are already close to terminological definitions. On the other hand, we can identify some more atypical features for dictionaries at the level of the macrostructure. The most obvious one is that, in some places, information about the term is given outside the dictionary entry. The second is that the book does not contain an alphabetical list of skiing terms.
Keywords: skiing terminology; historical linguistics; terminography; Rudolf Badjura